Cos(2x) = cos^2(x) - sin^2(x) - cos(x)
but sin^2(x) = 1 - cos^2(x)
cos(2x) - cos(x) = cos^2(x) - (1 - cos^2(x) ) - cos(x)
cos(2x) - cos(x) = cos^2(x) - 1 + cos^2(x) - cos(x)
cos(2x) - cos(x) = 2cos^2(x) - 1 - cos(x)
cos(2x) - cos(x) = (2cos(x) + 1)(cos(x) - 1)
I think this is what you have asked for.
Answer:
A^k/b^k
Step-by-step explanation:
A/b^k=a^k/b^k
Answer:
B and C
(I'm not sure if b and e are supposed to be the same though) if they are then, b, c, and e
Answer:
85
Step-by-step explanation:
10x13=130, 9x5=45, 130-45=85